Added Value of Postoperative Radioiodine Scan for Staging and Risk Stratification in Papillary Thyroid Microcarcinoma - Kaewchur, Tawika; Namwongprom, Sirianong; Waisayanand, Nipawan; Pongwiwattanachai, Waralee; Ekmahachai, Molrudee (Journal of the ASEAN Federation of Endocrine Societies, 2021)
<center> </center><center>*Visual Abstract prepared by Dr. Jerico Gutierrez</center> Objective. The complete staging and risk stratification of Papillary thyroid microcarcinoma (PTMC) is usually not done due to its theoretically low recurrence rates. This study aimed to determine the value of postoperative radioiodine diagnostic scan and SPECT/CT for the accurate staging and risk stratification in PTMC patients. Methodology. This study was a retrospective review of PTMC patients from January 2014 to May 2017 who underwent I-131 scans. All PTMC patients were initially staged by the 8th edition AJCC/TNM staging system and risk-stratified, based on clinical information, histopathology and stimulated thyroglobulin (sTg). After I-131 scan, staging and risk stratification were re-assessed. The proportion of patients who ended up with a higher stage and risk stratification were reported. Results and Conclusion. Fifty-two patients were included. The overall upgrading of cancer stage was 7.7 %. The overall higher risk stratification was 19.2% with radioiodine-avid lymph node, lung, and bone metastases. Neck and paratracheal node metastases were found in 37.3% of the initial low-risk patients with sTg less than 5 ng/mL. Lung metastasis was found in the initial intermediate-risk patient. The I-131 scan helps to localize metastatic lesions and results in a higher stage in 50% of the initial high-risk patients. This study provides some evidence showing the value of postoperative radioiodine WBS for accurate staging and risk stratification in PTMC patients. Larger studies with analytical design should be further performed to prove its significant utility.